The force of truth: critique, genealogy, and truth-telling in Michel Foucault - Lorenzini, Daniele (Chicago, USA; London, UK: The University of Chicago Press, 2023)
"It has become fashionable in certain intellectual circles to trace our present of alternative facts and denialism back to Foucault and what critics claim to be the way he undermines the stable notion of truth. In The Force of Truth, Daniele Lorenzini explains why this understanding of Foucault stems from a fundamental misreading of his work. Foucault was not interested in defining what truth is, nor in elaborating or defending a specific theory of truth. Instead, Lorenzini shows, Foucault's project of a history of truth aims to trace the genealogy of the main regimes of truth that have emerged throughout human history and are relevant for us today. In this fundamental re-reading of Foucault's critical project as a whole, The Force of Truth provides a new understanding of Foucault's history of truth and a clear statement on one of the most pressing matters concerning Foucault's legacy. Foucault does not reduce the question of truth to a purely logical or epistemological question, or to the philosophical task of elaborating a definition or theory of truth; he constantly asks us to be surprised by the proliferation of true discourses throughout human history, and never to take for granted their emergence and existence"--
Introduction : writing the history of truth -- Truth-event -- Regimes of truth -- Truth as force -- Dramatics of truth -- Critique and possibilizing genealogy -- Conclusion : rethinking critique.
Originally published as La force du vrai : de Foucault à Austin.
Translated, revised, and expanded by the author.
Includes bibliographical references (pages 175-191) and index.
Keywords: Foucault, Michel, -- 1926-1984.; Foucault, Michel